Better than one: a synthetic community of Gram-positive bacteria protects pepper plants from aphid infestation through de novo volatile production - Lee, Sang-Moo; Yang, Hyeonu; Kong, Hyun Gi; Riu, Myoungjoo; Ryu, Choong-Min (Frontiers in Plant Science, 2025)
Soil microbes offer various benefits to plants, including induced systemic resistance and growth promotion, with some functioning as biocontrol agents. Although the role of microbial consortium in microbiota function was recently elucidated, the production of a specific determinant through microbial cooperation for plant protection against insect infestation has not been demonstrated to date. Here, we report that a synthetic community (SynCom) comprising four Gram-positive bacteria could protect pepper plants from aphid infestation under greenhouse and field conditions. Headspace solid-phase microextraction-gas chromatography mass spectrometry analysis of the determinants produced by the four bacteria during co-cultivation led to the de novo detection of a volatile compound, 1-nonanol. Drench application of 1 mM 1-nonanol reduced aphid infestation. Taken together, our results suggest that SynCom and its volatile compound can effectively attenuate insect infestation. This is the first case study demonstrating how a volatile compound synthesized in the rhizosphere soil by bacteria protects plants against invasion by a sucking insect pest.